Screening soybean lines for heat-tolerant pollen - Walker, Levi P. (Kansas State University, 2012)
Heat and drought stress are common problems for crops grown in Kansas. Rarely do these problems occur separately, more often than not they occur in tandem if not simultaneously. The interaction of heat stress and pollen germination was investigated in order to determine if a physiological screen was a feasible method of determining heat tolerance in soybean [Glycine max (L.) Merr]. Ten soybean lines (Group A) from the 2006 Northern Region Uniform Soybean Tests were analyzed over two years in four locations consisting of irrigated and dryland field environments, with an additional twenty lines (Group B) analyzed in the second year. Pollen was collected from plants and incubated at either 28o, 34o, or 38o C to determine pollen germination for optimal and stress-inducing temperatures. A three-way interaction of entry x incubation temperature x environment was observed, as well as significant differences among entries, incubation temperatures and environments. Average pollen germination for soybean entries ranged from 25% to 38% across three incubation temperatures and four environments in Kansas during 2006 – 07. The average environment effect for pollen germination ranged from 29% (dryland, 2006) to 34% (irrigated, 2007), while the average incubation temperature effect on pollen germination ranged from 25% (38oC) to 44% (28oC). This experiment has shown that increasing incubation temperatures significantly decreases pollen germination in vitro. It has also shown that soybean genotypes differ in pollen germination and that an in vitro screen can be used to characterize these differences. Further studies are needed to establish the relationship between pollen germination, seed set and seed yield in soybean. Work also needs to be completed to determine the proper sample size to adequately characterize differences in pollen germination so that performance differences among genotypes can be used as selection criteria in a plant breeding program.
Keywords: pollen; heat tolerance; soybean; glycine max; Agronomy (0285); Plant Sciences (0479)